Q. 225.0( 1 Vote )

Mark the correct

Answer :

Given that f : R –{n} R where



Let f(x) = f(y)



(x-m)(y-n)=(x-n)(y-m)


xy – xn – my + mn = xy – xm – ny + mn


x = y


So, f is one-one.




y(x-n)=(x-m)


xy – ny = x – m


x(y-1) = ny – m



For y = 1 , no x is defined.


So, f is into.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar